Hubungan Antara Kebiasaan Belajar dengan Hasil Belajar Biologi Pada Angkatan 2018 di UMMY Solok - Helvita Roza (Eduscience Development Journal, 2019)
This research is motivated by good study habits, including paying attention, noting essential things, doing assignments, having regular study time, and a high interest in learning. However, not all students have good study habits; many have difficulty understanding. Then, research will be conducted with the title "there is a relationship between study habits and biology learning outcomes in the 2018 class at UMMY Solok" which aims to describe the student's study habits and their relationship to biology learning outcomes in the 2018 batch at UMMY. This type of research is descriptive. The goal is to solve problems that exist in the present, provide a general description of the data obtained and draw conclusions from the results of data processing. The population of this study was biology students in the 2018 class at UMMY who were registered in the 2018/2019 academic year. The sample selected in this study were biology students in the 2018 class at UMMY in the even semester of the 2018/2019 academic year. Data was collected using a questionnaire. The data obtained were processed using a simple linear regression technique.